3D FEM approach for laterally loaded monopile design. (August 2018) - Murphy, Gerry; Igoe, David; Doherty, P.; Gavin, K.
Abstract: Over the past 5 years, a substantial research effort aimed at optimising the design of offshore wind turbines has led to significant reductions in the projected cost of developing offshore wind. Optimising the geotechnical design of these structures, through modern analysis techniques such as 3D Finite Element Modelling (FEM), has played a key role in helping to reduce costs. This paper presents a methodology for accurately modelling monopile behaviour using Cone Penetration Test (CPT) data to calibrate the non-linear stress dependent Hardening Soil (HS) model. The methodology is validated by comparing the modelled behaviour to field tests on a range of pile geometries. The paper also demonstrates how the soil-pile reaction response curves can be extracted from the FE model by isolating the stresses on each element of the pile. The contribution of each component to the overall lateral resistance is shown to vary with the pile geometry and is examined using the extracted soil reaction curves.